(untitled) (Bioagro, 2024)
The generation of information that serves as an argument in the search for alternatives for sustainable management of irrigation in rice is an inevitable current demand. Given this, this study aimed to evaluate traditional irrigation (continuous flooding) through crop production, water use efficiency and methane emission; taking as reference an irrigation alternative without flooding (aerobic), in which soil moisture was maintained between saturation and around field capacity. With these two irrigation alternatives, an experiment of four square plots of 25,0 m on each side was installed, defining nine sampling points of 4,0 m2 within each of them. The INIAP 11 rice variety for local use was used, with sowing by transplant. Irrigation management was carried out under the evaporation tub method, together with the registration of tensiometers in humidity control. In the crop, tillering, empty grains (%), weight of 1000 grains (g) and yield (kg·ha-1) were evaluated. For the measurement of methane, two acrylic chambers of 1,0 m x 1,0 m x 1,2 m were used, together with a portable gas and temperature meter. No significant differences were detected in crop production, a substantial increase in water use efficiency from 3,649 m3·kg-1 to 0,312 m3·kg-1. The methane emission rate was significantly (P≤0,05) higher in traditional irrigation, with an average of 2,92 mg·m-2·h-1; while, in aerobic irrigation, this value was 1,07 mg·m-2·h-1. It was concluded that the proposed irrigation alternative has advantages in all the parameters evaluated with respect to traditional irrigation.